Screening of potential enzyme producers from microorganisms isolated from soil and compost material (agricultural solid waste) / Wan Razarinah Wan Abdul Razak, Ernie Eileen Rizlan Ross and Rafidah Rasol. - Wan Abdul Razak, Wan Razarinah; Rizlan Ross, Ernie Eileen; Rasol, Rafidah (2006)
This study was aimed at isolating and screening of fungi from various soil and agricultural solid waste for potentiality in producing the industrially important cellullase and protease enzymes. As many as fourteen different fungi strains were successfully isolated from ten samples of soil namely backyard soil, palm oil soil, chicken farm soil, laterite soil, paddy field soil, cocoa farm soil, forest soil, riverbank soil, compost soil and peat soil using the pour plate method on Potato Dextrose Agar (PDA). Eight out of fourteen isolated fungal isolates showed the ability of producing protease enzyme as demonstrated by the production of clearing zone on Skim Milk Agar (SMA). Four of them showed morphological characteristics similar to those of Aspergillus spp, while three other strains showed similar characteristics to fungi of the Order Mucorales. Meanwhile, one strain showed characteristics similar to fungi under the Class Trichomycetes. On the other hand, as many as eighteen different fungal isolates were successfully isolated from eight different agricultural solid waste samples namely dried palm seeds, squeezed palm seeds, palm bunch, coconut dregs, coconut husks, sugar cane dregs, corn bunch and paddy hays . Out of the eighteen isolated fungi, twelve of them were found to be able to produce protease enzymes as demonstrated by the production of clearing zone on Skim Milk Agar (SMA). Five of the potential isolates resemble the characteristics of Aspergillus spp., while two of them have similar characteristics to Penicillium spp. Two have the characteristics of Microsporium spp. and one of them shows similar characteristics to Mucor spp.